Distribution Of Extractable In Soils Of Selected Major Land Resource Area OF Kerala - Sathyanarayanan R (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1997)
The investigation was carried out to assess the total and available micronutrients in soils of selected major land resource areas (MLRAs) of' Kerala. The micronutrients investigated in the present study were iron, manganese, zinc, copper and boron. The study was intended to establish the pattern of the distribution of micronutrients both vertically and spatially in eight MLRAs viz, Palode, Vellayani, Trivandrum, Mannar, Kottarakkara, Thakazhy, Ramankary and D-Block soil series of Kerala. Three extractables viz DTPA, EDTA and ammonium acetate were used in the analysis. The available boron content in these soils was also determined by hot water extraction method. All the micronutrients showed great variation in their distribution in the various horizons of the profiles. The micronutrients content of the soils estimated were correlated with soil properties like pH, organic carbon, CEC and clay content. They were found to be positively and significantly correlated with organic carbon, CEC and clay content while it was significantly and negatively correlated with pH. The significant correlations revealed that the micronutrient availability in these soils were influenced greatly by the soil properties mentioned above. From the results obtained, it was observed that micronutrients like iron and manganese were well supplied in all the profiles studied. The micronutrients